Atomically Dispersed High‐Density Al–N4 Sites in Porous Carbon for Efficient Photodriven CO2 Cycloaddition. Issue 45 (18th September 2021) - Yang, Qihao; Peng, Huaitao; Zhang, Qiuju; Qian, Xu; Chen, Xu; Tang, Xuan; Dai, Sheng; Zhao, Jiajun; Jiang, Kun; Yang, Qiu; Sun, Jian; Zhang, Linjuan; et al.
Abstract: Highly active catalysts that can directly utilize renewable energy (e.g., solar energy) are desirable for CO2 value‐added processes. Herein, aiming at improving the efficiency of photodriven CO2 cycloaddition reactions, a catalyst composed of porous carbon nanosheets enriched with a high loading of atomically dispersed Al atoms (≈14.4 wt%, corresponding to an atomic percent of ≈7.3%) coordinated with N (AlN4 motif, Al–N–C catalyst) via a versatile molecule‐confined pyrolysis strategy is reported. The performance of the Al–N–C catalyst for catalytic CO2 cycloaddition under light irradiation (≈95% conversion, reaction rate = 3.52 mmol g −1 h −1 ) is significantly superior to that obtained under a thermal environment (≈57% conversion, reaction rate = 2.11 mmol g −1 h −1 ). Besides the efficient photothermal conversion induced by the carbon matrix, both experimental and theoretical analysis reveal that light irradiation favors the photogenerated electron transfer from the semiconductive Al–N–C catalyst to the epoxide reactant, facilitating the formation of a ring‐opened intermediate through the rate‐limiting step. This study not only provides an advanced Al–N–C catalyst for photodriven CO2 cycloaddition, but also furnishes new insight for the rational design of superior photocatalysts for diverse heterogeneous catalytic reactions in the future. Abstract : A porous carbon possessing atomically dispersed Al–N4 motifs exhibits excellent catalytic performance for photothermal CO2 cycloaddition reaction by taking advantage of the uniformly dispersed Al/N species and the efficient photothermal effect of the carbon matrix. Importantly, the photogenerated electrons favor transfer from Al–N–C to epoxide and significantly accelerate the rate‐limiting step, which opens a new activation mechanism for CO2 cycloaddition reaction.